2012
DOI: 10.5897/ajbm12.523
|View full text |Cite
|
Sign up to set email alerts
|

Alignment in the organizations strategy window (concentration on business strategy and operations strategy)

Abstract: Nowadays, strategy is defined at corporate, business and functional level. The success of the organizations depends not only on developing strategies at these levels but also alignment between them. In this paper, by delineating strategy levels and their differences, a window called organization's strategy window is introduced and then the concept of alignment and the method of alignment in the organization's strategic window are explained. Strategic alignment is divided into the two types: vertical alignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…(3) Market instincts. It has a faster sense of market change and can sense and respond to customer needs, competitors' activities and emerging markets (Hossain et al, 2012). (4) Double segmentation.…”
Section: Resultsmentioning
confidence: 99%
“…(3) Market instincts. It has a faster sense of market change and can sense and respond to customer needs, competitors' activities and emerging markets (Hossain et al, 2012). (4) Double segmentation.…”
Section: Resultsmentioning
confidence: 99%
“…As an early leader in the discussion, Porter [9] described the competitive strategy as the selection of actions leading to firm competitiveness in an industry or market. Salimian et al [10] defined strategies as decisions on the future positions of organizations and the ways by which to arrive at these positions. Ho [11] saw strategy as incorporating all of an organization's actions from various functional units.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on a resource-based approach, Johnson and Scholes [12] explained strategy as an organization's selection for performing activities that correspond with its environment and available resources. Salimian et al [10] also indicated that strategy was defined at the corporate (top), business (middle), and functional (bottom) levels, with the success of the organization depending on not only formulating strategies at these levels but also aligning the strategies. To integrate the various definitions presented by previous researchers, strategy here means decision making about focusing or spending resources on selected activities, after analyzing the internal and external environment, to achieve the organization's objectives and desired future position.…”
Section: Literature Reviewmentioning
confidence: 99%